2009
DOI: 10.1007/s00595-009-3957-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hypocalcemia occurring after a total/near total thyroidectomy

Abstract: Intact parathormone measurement 10 min after SC is helpful to predict early postoperative hypocalcemia. An IPTH decrease >/=30% at this time point estimates the risk of postoperative hypocalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
1
26
0
2
Order By: Relevance
“…Some investigators have proposed serial measurements of calcium (6, 12, and 20 h or 8, 14, and 20 h) as a protocol for monitoring postthyroidectomy patients (16)(17)(18)(19). Others (7-9) have suggested combining intact parathyroid hormone (PTH) and serum calcium measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have proposed serial measurements of calcium (6, 12, and 20 h or 8, 14, and 20 h) as a protocol for monitoring postthyroidectomy patients (16)(17)(18)(19). Others (7-9) have suggested combining intact parathyroid hormone (PTH) and serum calcium measurements.…”
Section: Discussionmentioning
confidence: 99%
“…1,[8][9][10][11][12] A surgeon needs to know whether the parathyroid glands are at risk during surgery, because persistent hypoparathyroidism is a harrowing condition. A stable or increased intraoperative PTH concentration rules out the possibility of persistent hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Kara et al reported that 54% of patients who underwent either a total or near total thyroidectomy develop transient hypocalcemia. 1 Hypocalcemia is self-limiting in most patients and does not require treatment; however, symptomatic hypocalcemia is of particular concern. Symptoms usually manifest 24 to 48 h after the operation, and it is not usually easy to predict which patients are prone to the development of this complication and will require calcium and/or vitamin D supplements.…”
Section: Introductionmentioning
confidence: 99%
“…Das intraoperative Monitieren der Funktion des N. laryngeus recurrens kann dieses Trauma nicht minimieren. Postoperativ kann die Kompression durch ein lokales Hämatom ursäch-lich sein [7,8,9,10].…”
Section: Ursachenunclassified